2019
DOI: 10.1002/cam4.1302
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: lncRNA HOTAIR promotes gastric cancer proliferation and metastasis via targeting miR‐126 to active CXCR4 and RhoA signaling pathway

Abstract: HOTAIR, a well‐known long noncoding RNAs (lncRNA), has been recognized to contribute to the tumor metastasis in several tumors. But its role in gastric cancer remains elusive. Here, we reported an increase in HOTAIR promoted proliferation and metastasis of gastric cancer cell lines. The HOTAIR and miR‐126 level was determined in 15 paired primary gastric cancer tissues and their adjacent noncancerous gastric tissues. Over‐expression or downregulation HOTAIR was conducted in AGS or BGC‐823 cells to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…Recently, increasing evidence indicates that a large number of lncRNAs are dysregulated in GC. [24][25][26] The dysregulation of lncRNAs is implicated in the regulation of various malignant cytological behaviors during gastric carcinogenesis and GC progression. [27][28][29] Therefore, comprehensive research into the lncRNA-based regulatory network in GC may facilitate the discovery of effective targets for the diagnosis and treatment of this cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, increasing evidence indicates that a large number of lncRNAs are dysregulated in GC. [24][25][26] The dysregulation of lncRNAs is implicated in the regulation of various malignant cytological behaviors during gastric carcinogenesis and GC progression. [27][28][29] Therefore, comprehensive research into the lncRNA-based regulatory network in GC may facilitate the discovery of effective targets for the diagnosis and treatment of this cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the ceRNA network between lncRNAs and miRNAs may help expand our understanding of the possible mechanism of hepatic fibrosis [20,36,42]. DE lncRNAs, miRNAs and mRNAs in mice were obtained from the National Center for Biotechnology Information (NCBI) database (miRNAs in GSE7727, lncRNAs and mRNAs in GSE80601) [43].…”
Section: Lncrnas Are Widely Expressed In Animal Modelsmentioning
confidence: 99%
“…The lncRNA Hotair located in the homeobox complex (HOXC) locus has been studied extensively in cancer, and the findings strongly suggest that Hotair promotes cancer progression [21,22,42,84]. Bian et al found that Hotair was significantly upregulated in CCl 4 -induced human fibrotic livers, mouse liver fibrosis models, and HSCs activated by TGF-β1 stimulation [60].…”
Section: Hotairmentioning
confidence: 99%
“…However, lncRNAs may be involved in different biological processes with different functions, which need to be taken into consideration before lncRNAs are used in clinical setting. [ 73,74 ]…”
Section: Reagents Involved In Selective Protein Degradationmentioning
confidence: 99%